Eureka Role Playing Game: An Instructional Tool In Improving The Proficiency Level In Chemistry 7 - C. Bacho, Ma. Maybelle; C. Dimanarig, Ginalyn; B. Gache, Cris Nelson; B. Garcia, Lenber; B. Hermoso, Ed Christian; A. Ramuyan, Honey Camille; D. Cronico, Andrei (International Journal of Educational Management and Innovation, 2024)
The Eureka Role Playing Game is a game-based instructional tool for learning science concepts. The study aimed to improve proficiency level of the learners in Science 7 particularly in Chemistry subject. This study utilized a Quantitative Method to measure the gathered data and test the hypothesis. Quasi-experimental pretest-posttest research design was also used with a validated questionnaire and Eureka Role-Playing Game (RPG) as the primary data gathering instrument to evaluate students’ proficiency level improvement as the intervention was administered to experimental group and traditional teaching method for controlled group. Results showed that in the controlled group, the mean post-test result was higher than the mean pre-test result, but still at the beginning level of proficiency. Meanwhile, the mean post-test result of the experimental group is higher compared to the mean pre-test result. Therefore, the level of proficiency of the experimental group has improved from a beginning level to a developing level after the intervention. A significant difference in the pre-test and post-test between the experimental group and the control group is in favor of the experimental group. Therefore, the alternative hypotheses of this study are accepted. Evaluated by the Science experts, the instructional tool passed the curricular validity criteria. The researchers recommend the use of Eureka Role Playing Game since it significantly increased the proficiency level of the students from beginning to developing level based on the findings.